Gonilni mehanizmi kavitacijskega vrtinca v vstopnem vodu radialne črpalke - Predin, Andrej (Strojniški vestnik, 2001)
Analyses are given of the driving mechanisms and pressure pulsations relating to the cavitation swirl in the entrance pipe of a radial pumpe. The appearance of cavitation swirl is a result of a complicated secondary flow interaction, which appears as a consequence of the pump operating at small, under-optimum capacities in the cavitation operating regime. Results of the flow pressure pulsation measurements in the entrance pipe of the radial pump are reported. These measurements were made at different distances from the impeller eye, in the upstream direction at the closed cavitation measuring test ring with the pump operating at different impeller speeds and at different values of gas (air) pressure over the lower liquid (water) position. Results are also given for the frequency analyses of the measured flow pressure.
Keywords: črpalke radialne; vrtinci kavitacijski; režimi obratovanja; meritve tlačnih utripov; radialne črpalke; kavitacija; obratovanje